Pore size characteristics of needle-punched nonwoven geotextiles under laterally constrained condition - Chen, W. L.; Xia, Q. Y.; Li, K. Y.; Qiu, J.; Chen, X. L.; Tang, X. W. (Frontiers in Materials, 2025)
The effects of lateral constrained uniaxial tensile strain on the tensile behavior of needle-punched nonwoven geotextiles were investigated. Tests were conducted on geotextile specimens using a clamping device that imposed lateral constrained strains. The pore size characteristics of geotextiles were obtained using bubble point method (BBP) test. An extended pore size distribution (PSD) model for nonwoven geotextile subjected to lateral constrained uniaxial strain condition was proposed. A finite element method (FEM) model of the geotextile was established to model the tensile behavior of geotextiles under later constrained tensile strains. The experimental results obtained by the BBP tests were analyzed, and the theoretical and simulated values were compared with the BBP-based values. It is showed that the PSD curves of geotextiles shifted towards larger sizes under tensile strain, with insignificant shape changes. The five characteristic pore sizes (O95, O80, O50, O30, O10) exhibited a consistent increasing trend. The theoretical and simulated PSD curves for geotextiles steadily shifted towards larger sizes, maintaining consistent shapes as tensile strain increased. Both the theoretical and FEM models accurately predicted the variations in the experimental O95. For the theoretical model, the correlation coefficients were 0.90 and 0.9962 respectively; for the FEM model, the correlation coefficients were 0.9481 and 0.9866 respectively.